TurboTAX for DOS: Tax preparation and planning software for IBM Standard Personal Computer version 9 - 1992 for the 1991 tax year and 1992 tax planning (San Diege, California, 1991)
The book consists of 9 chapters. Chapter 1 explains how to start TurboTax, to begin tax return, to save tax return information, to quit Tax and to resume working on tax return. Chapter 2 guides to use TurboTax. Chapter 3 reviews the basic elements of a federal income tax return, explains the kinds of records, and discusses the new laws and changes in the tax forms for 1991. Chapter 4 details everything about entering data. Chapter 5 provides the checking Tax return. Chapter 6 guides how to print tax return. Chapter 7 is filing tax return. Chapter 8 explains how to use TurboTax to keep records for 1992 tax return, carry out tax planning and analysis for 1992. Chapter 9 explains the services that are available as a ChipSoft customer. Appendix A through Appendix F provide deatails about certain optional program features and complex tax topics> Appendix G discusses unusual situations that can occur and explains how to resolve
Keywords: TAX ( computer program language )